Utilization of Information Technology and Management of Organizational Change in the Recovery of the Economic Sector in MSMEs (Case Study of MSMEs in Cianjur Regency After the Earthquake Natural Disaster) - Ayu, Retno Barunawati; Nurhaeni, Ismi Dwi Astuti; Utari, Prahastiwi (AIBPM Publisher, 2023)
The earthquake natural disaster that occurred in Cianjur Regency on November 21 2022 had paralyzed all sectors including the economic sector which is one of the most important sectors supporting the progress of residents in Cianjur Regency. Like regions in Indonesia whose economic factors can progress because of the help of regional MSMEs, Cianjur Regency has also shown quite rapid development, and can become one of those that play an important role in the economy of the people in this area. The Office of Cooperatives, Small and Medium Enterprises, Trade and Industry (Diskoperdagin) of the Cianjur Regency noted that as of January 2023 there had been 15 new MSME groups requesting assistance and training in improving MSMEs in Cianjur Regency. The purpose of this study is to examine how information technology and organizational change management can support MSME actors in Cianjur Regency in recovering the economic sector after the earthquake. This is very important to do in order to increase productivity and progress of the company. Preparing the company from all transitions of change and business competition and reducing all obstacles and risks that occur from a product being marketed.